Irregularities in conducting the list of assets and liabilities - Jakovljević Nemanja (Trendovi u Poslovanju)
Irregularities that may occur during the preparation and conduct of the inventory of assets and liabilities may have serious and multiple implications for the entity's financial statements and its results of operations. This is conditioned by the fact that the inventory as a part of the pre-closing postings represents the basis for reducing the bookkeeping to the actual situation. The census can determine the existence of undocumented economic changes, for which at the time of their occurrence there was no adequate document to confirm their existence and their value impact on the operations of the entities. Improper conduct of the census can be sampled by intentional actions aimed at presenting incorrect facts in an attempt to present a better business result in the financial statements than it really is, which would benefit one stakeholder to the detriment of other stakeholders. For these reasons, it is important to understand the irregularities that occur during the census in order to prevent and disable their occurrence in practice.